The Butler Collection - Earley, Sylvia A. (Trinity College (Dublin, Ireland). Department of History, 2000)
The Butler Library, the topic of this thesis, is a collection of books which was given to Trinity College in the late eighteenth century. Theophilus Butler, Baron Newtown-Butler, a Dublin based politician who died in 1723, was the main contributor to the collection. The books are currently housed in the Long Room of the Old Library and can be seen to the north of the library. Despite the fact that the books are still used individually by students in the college today little work has been done on the collection itself or its history. The only major article written in relation to any part of Butler's collection has been James Wooley's John Barrett, "The Whimsical Medley", and Swift's Poems. ...
Keywords: History, M.Phil.; Reformation and Enlightenment Studies, M.Phil.; M.Phil. Trinity College Dublin